PRECISION MEDICINE AND CLINICAL PHARMACISTS - Jacson Mandumpala, Janice (Indian Journal of Pharmacy & Drug Studies, 2024)
The term "bedside pharmacist" also applies to clinical pharmacists. Pharmacists are in a position to take the lead in pharmacogenomic testing, clinical interpretation of data, and recommendations for individualized medication therapy because pharmacogenomic testing can offer patient-specific predictors for drug response. There are career paths for pharmacists in both inpatient and outpatient settings, including managing clinical pharmacogenomics consultation services and teaching families and patients about pharmacogenomic screening. Therefore, clinical pharmacists play a crucial role in improving lives through proper medical management. The pharmacy curriculum includes coursework that offers opportunities to gain knowledge and skills in pharmacogenomics. These opportunities also extend to postgraduate education (such as residencies, fellowships, and continuing education). The Clinical Pharmacy Advocacy Group emphasizes the need for improved training for chemists in practice as well as students to take precision medicine into account. This review elaborates on the scope of precision medicine, its applications, and the role of a clinical pharmacist in advocating this practice.